THU0006 Novel Changes in B and T-Cell Phenotypes with Belimumab in An Autoantibody Mediated Disease. (15th July 2016) - Barrett, C.; Henderson, R.B.; Galwey, N.; Flint, S.; Gibson, A.; Savage, C.
Abstract : Background: Belimumab is a B-lymphocyte stimulator (BLyS)-specific inhibitor indicated for the treatment of adult patients with active, autoantibody-positive, systemic lupus erythematosus. Belimumab has also been shown to reduce anti-phospholipase A2 receptor (PLA2R) autoantibodies and proteinuria in a mechanistic study in primary membranous nephropathy (PMN) 1 . Here we report an interim analysis of B and T cell phenotypes in PMN subjects treated with belimumab to further elucidate the mechanism of action in autoantibody mediated disease. Objectives: To characterize changes in B and T lymphocyte phenotypes in PMN patients treated with belimumab, as a comparison with known pharmacodynamic (PD) effects in SLE 2, and to assess correlation with anti-PLA2R autoantibody. Methods: 14 anti-PLA2R autoantibody positive PMN patients received 10mg/kg iv belimumab every 4 wks (or 2 wks) for up to 100 wks. 11 of these completed at least 28 wks treatment. Whole blood was collected at baseline, Wks 8, 16 and 28 for analysis of B and T-cell phenotypes by flow cytometry. Serum levels of anti-PLA2R antibodies were measured by ELISA (Euroimmun). Statistical analysis to identify PD-induced changes in lymphocyte subsets was carried out by paired t-test (2 tailed) against baseline. Correlations between anti-PLA2R antibody and B and T-cell subsets, either at a specific time point or in the linearised trend over time, were calculated using Pearson's correlation coefficient (r). Results: There was a significant reduction (-63%, p=0.002) in absolute numbers of naive B cells (CD19+ CD27-) at Wk 8 which was sustained through to Wk 28. There was a significant increase in absolute numbers of memory B cells (CD19+ CD27+) at Wk 8 (70%, p=0.023) which increased further through to Wk 28. Plasmablasts (or SLE subset, CD19lo CD38hi CD27hi) showed a trend at Wk 8 to decrease (-64%, p=0.20) but with high variance and low cell numbers. In addition, the expression (mean fluorescence intensity) of BAFF-R (B-cell activating factor receptor) on B-memory cells increased through Wk 28, while expression of TACI (transmembrane activator and calcium modulator and cyclophylin ligand interactor) decreased. Activated cells as identified by surface CD95 expression, decreased as a proportion of B-memory cells through Wk 28. No clear trend was seen in T-regulatory or T-activated cells. There was a significant negative correlation between decrease in absolute numbers of naive B-cells and immunological efficacy defined as level of anti-PLA2R antibody remaining at Wk 28 (r=-0.87, p=0.0005). Correlations were also seen between antibody and changes in proportion of B-memory CD95+ cells. Conclusions: This mechanistic trial of belimumab in PMN has enabled a novel analysis of PD endpoints, confirming but also extending the PD effects previously reported in studies of SLE. Changes in B-cell subsets were associated with improvements in levels of autoantibody in PMN which in turn correlates with proteinuria. Further analysis of longer term anti-PLA2R antibody kinetics as related to early changes in B and T cell phenotypes may also be informative. References: Willcocks L, Barrett C, Brenchley P et al. Nephrology Dialysis Transplantation. 2015; 30 (Supplement 3): iii32–iii33. Stohl W, Hiepe F, Latinis KM et al. Arthritis & Rheumatism. 2012;64(7):2328–2337. Acknowledgement: This study was funded by GSK (study sponsor) (BEL116472, NCT01610492 ). Disclosure of Interest: C. Barrett Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, R. Henderson Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, N. Galwey Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, S. Flint Grant/research support from: GlaxoSmithKline, A. Gibson Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, C. Savage Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline